Controls on the Silicon Isotope Composition of Diatoms in the Peruvian Upwelling - Grasse, Patricia; Haynert, Kristin; Doering, Kristin; Geilert, Sonja; Jones, Janice L.; Brzezinski, Mark A.; Frank, Martin (Frontiers in Marine Science, 2021)
The upwelling area off Peru is characterized by exceptionally high rates of primary productivity, mainly dominated by diatoms, which require dissolved silicic acid (dSi) to construct their frustules. The silicon isotope compositions of dissolved silicic acid (δ30dSi) and biogenic silica (δ30bSi) in the ocean carry information about dSi utilization, dissolution, and water mass mixing. Diatoms are preserved in the underlying sediments and can serve as archives for past nutrient conditions. However, the factors influencing the Si isotope fractionation between diatoms and seawater are not fully understood. More δ30bSi data in today's ocean are required to validate and improve the understanding of paleo records. Here, we present the first δ30bSi data (together with δ30dSi) from the water column in the Peruvian Upwelling region. Samples were taken under strong upwelling conditions and the bSi collected from seawater consisted of more than 98 % diatoms. The δ30dSi signatures in the surface waters were higher (+1.7 ‰ to +3.0 ‰) than δ30bSi (+1.0 ‰ to +2 ‰) with offsets between diatoms and seawater (Δ30Si) ranging from -0.4 ‰ to -1.0 ‰. In contrast, δ30dSi and δ30bSi signatures were similar in the subsurface waters of the oxygen minimum zone (OMZ) as a consequence of a decrease in δ30DSi. A strong relationship between δ30bSi and [dSi] in surface water samples supports that dSi utilization of the available pool (70 % and 98 %) is the main driver controlling δ30bSi. A comparison of δ30bSi samples from the water column and from underlying core-top sediments (δ30bSised.) in the central upwelling region off Peru (10°S and 15°S) showed good agreement (δ30bSised. = +0.9‰ to +1.7‰), although we observed small differences in δ30bSi depending on the diatom size fraction and diatom assemblage. A detailed analysis of the diatom assemblages highlights apparent variability in fractionation among taxa that have to be taken into account when using δ30bSi data as a paleo proxy for the reconstruction of dSi utilization in the region.